The Impact of Artificial Intelligence (AI) in Content Personalization on Customer Experience and Purchase Intention among Generation Z Users of Shopee Indonesia: A Study of Aerostreet Footwear Consumers - Randy Satya Ramadhani; Any Urwatul Wusko (Darul Yasin Al Sys, 2026)
The advancement of digital technologies and the adoption of artificial intelligence (AI) on e-commerce platforms have transformed consumer–business interactions through increasingly personalized content delivery. However, the effectiveness of AI-driven personalization in enhancing customer experience and stimulating purchase intention among Generation Z e-commerce users in Indonesia remains insufficiently understood. This study examines the influence of AI-based content personalization on customer experience and purchase intention and investigates the mediating role of customer experience in this relationship. A quantitative approach with a causal-associative research design was employed. Data were collected through questionnaires administered to 384 Generation Z users of Shopee Indonesia who had interacted with Aerostreet footwear products and were analyzed using partial least squares structural equation modeling (PLS-SEM). The findings indicate that AI-based content personalization positively influences both customer experience and purchase intention. Customer experience also positively influences purchase intention and mediates the relationship between AI-based content personalization and purchase intention. These findings demonstrate that customer experience represents an important mechanism through which AI-driven personalization shapes consumers’ purchase intentions. The study contributes to the digital marketing literature by clarifying the relationship among AI-based content personalization, customer experience, and purchase intention in the context of Generation Z consumers on an Indonesian e-commerce platform. Practically, the findings highlight the importance of relevant product recommendations and customer experience optimization in developing effective AI-driven digital marketing strategies.